Radio engineering for wireless communication and sensor applications - Räisänen, Antti V. (Artech House, 2003)
Covering a wide range of application areas, from wireless communications and navigation, to sensors and radar, this practical resource offers you the first comprehensive, multidisciplinary overview of radio engineering. You learn important techniques to help you with the generation, control, detection and utilization of radio waves, and find detailed guidance in radio link, amplifier, and antenna design. The book approaches relevant problems from both electromagnetic theory based on Maxwell's equations and circuit theory based on Kirchoff's and Ohm's laws, including brief introductions to each theory. Publisher abstract.
Keywords: Radio circuits.; Wireless communication systems -- Equipment and supplies.; Detectors.; Circuits radio.; TECHNOLOGY & ENGINEERING -- Mining.; Detectors; Radio circuits; Wireless communication systems -- Equipment and supplies; Andre fag (naturvidenskab og teknik) -- Andre fag